Broadband Optical Frequency Comb Generation With Flexible Frequency Spacing and Center Wavelength - Siyuan Yu; Fangdi Bao; Hao Hu (IEEE Photonics Journal, 2018)
A broadband optical frequency comb with a flexible frequency spacing and a center wavelength is proposed and experimentally demonstrated. The proposed scheme consists of a single continuous-wave laser, cascaded Mach–Zehnder modulator (MZM) and phase modulator (PM), two-stage dispersion-flattened highly nonlinear fibers (DF-HNLFs), and a single-mode fiber in between. A narrow-band frequency comb is generated in the MZM and PM, and a broadband frequency comb is achieved by a self-phase modulation based spectral broadening in the DF-HNLFs. Since the DF-HNLF has low dispersion over a wide wavelength range, the central wavelength of the generated frequency comb can be tuned from 1535 to 1564 nm. In addition, the central wavelength of frequency comb has a potential to be extended to L-band according to the dispersion profile of the DF-HNLF and the operation bandwidths of the MZM and PM. By tuning the driving radio-frequency signal, the frequency spacing of the generated frequency comb can be tuned. In the experiment, the frequency spacing of 25 and 40 GHz has been achieved.